PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN VOUCHER INTERNET XL PADA “KONTER KUSUMA” - Beti Mei Setiyaningrum; Supriyono Supriyono (STKIP Persada Khatulistiwa Sintang, 2022)
Internet is an important requirement for the community to be able to access information easily, besides that it is also a means of communication between humans. The rapid demand for internet services, especially for internet vouchers in Indonesia, is due to the increasing number of internet users in Indonesia. The use of the internet is not only for finding information but also for communicating. This study aims to determine and analyze the effect of price perceptions and promotions on purchasing decisions for XL internet vouchers (study at